Ferroelectric films for MEMS type devices using novel hybrid processing technology - Zhao, Chang Lei (2008)
Lead zirconate titanate (PZT) films are promising for MEMS type micro- devices applications because of their extremely high electromechanical coupling coefficients and excellent piezoelectric response. PZT piezoelectric film integrated on silicon substrate has been the subject of considerable attention in recent years. This thesis has presented a broad range of work, which aimed at developing, characterizing and evaluating PZT ferroelectric thick films for MEMS type device applications that could be integrated with silicon micromachining.